The authorship of place : a cultural geography of the new Chinese cinemas - Lo, Dennis (Hong Kong scholarship online., 2021)
'The Authorship of Place' is the first monograph dedicated to the study of the politics, history, aesthetics and practices of location shooting for Taiwanese, Mainland Chinese and coproduced art cinemas shot in rural communities since the late 1970s. Dennis Lo argues that rural location shooting, beyond serving aesthetic and technical needs, constitutes practices of cultural survival in a region beset with disruptive and disorienting social changes, including rapid urbanization, geopolitical shifts and ecological crises.